(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Fruits and vegetables produce the most food waste worldwide. Up to one-third of fruits and vegetables’ peels and skins are discarded during preparation and processing. India is ranked second in terms of fruit and vegetable output. This post-culinary waste can be managed by extracting it into a bio conservation energy and also used to make effective drugs on biological species. The study investigates the Cucurbita moschata, Cucurbita maxima, Cucurbita pepo L., Citrullus lanatus T., Cucumis melo L., Lagenaria siceraria, Cucumis sativa. species shows different pharmacological activities. All the pharmacological activities are the prospect of transforming post-culinary waste into highly nutritious food additives or supplements. Cucurbits have strong root systems that grow in the top 12 inches and taproots that reach three feet, allowing them to efficiently use nutrients and water from the soil. The content of Carbohydrate content of C. maxima, C. pepo, and C. moschata meat ranged from 26.23 ± 0.20 g/kg raw weight to 42.39 ± 0.84 g/kg and 133.53 ± 1.44 g/kg. C. maxima contained considerably more carbohydrates in pulp and peel than C. pepo or C. moschata. C. maxima exhibited considerably higher protein levels in the pulp (11.31 ± 0.95 g/kg raw weight) and peel (16.54 ± 2.69 g/kg raw weight) than C. pepo and C. moschata. C. pepo seeds had considerably higher protein (308.8 ± 12.01 g/kg raw weight) compared to C. maxima (274.85 ± 10.04 g/kg raw weight). C. pepo and C. moschata meat have a low-fat content (0.55 ± 0.14 and 0.89 ± 0.11 g/kg raw weight, respectively). C. pepo and C. moschata peels exhibited similar fat content (4.71 ± 0.69 and 6.59 ± 0.41 g/kg raw weight, respectively). C. maxima seeds contain considerably higher fat (524.34 ± 1.32 g/kg raw weight) than C. pepo or C. moschata (439.88 ± 2.88 and 456.78 ± 11.66 g/kg raw weight, respectively). C. pepo’s pulp and seeds had considerably less fiber and ash than C. moschata or C. maxima. C. maxima had the lowest moisture content, while all portions of C. pepo had the greatest.